Cultural Pedagogy in Practice: Embedding Torajan Heritage in Language Learning Resources - Elim Trika Sudarsi (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
This study explores how the integration of Torajan cultural elements into English language learning materials can enhance language acquisition and students’ understanding of local culture. Employing a qualitative approach, data were collected through observations and interviews with lecturers and students from the English Department. The findings reveal that the integration of Torajan culture in the classroom is achieved through curriculum adaptation, context-based approaches, and creative projects. Specific cultural elements included folklore (e.g., ulelean pare), traditional arts, dances, rituals, culinary heritage, traditional clothing, and everyday life in Toraja society. The study shows that embedding these cultural components had a highly positive and significant impact on students’ comprehension. It fostered greater engagement and motivation, improved language proficiency, deepened cultural awareness, and encouraged an appreciation for cultural diversity and multiculturalism. Additionally, the integration allowed students to form emotional connections with learning materials and strengthened their critical thinking, evaluative, and reflective skills. These findings suggest that the application of local cultural content not only enriches language learning but also contributes to students’ holistic development as culturally aware and globally competent individual.